Assessment of the role of interleukin 17A and interleukin 17F in chronic hepatitis C virus infection in Egyptian patients - Ahmed F Gomaa; Mohammed O Wahba; Raghda Abd El Lateif Hafez; Omar Mohamed Eldaly; Shahenda Gamal Badran (SpringerOpen, 2019)
Background/purpose of the study Chronic hepatitis C virus (HCV) infection is considered one of the major health problems. About 170 million patients were infected with HCV worldwide. Till few years, Egypt was considered the highest HCV prevalent country worldwide, with predominant genotype number 4. The host immunity plays a major role in HCV infection with evolving data confirming the role of T-helper 17 cells in the formation of chronic HCV infection. The aim of our work was to determine the role of interleukins 17A (IL17A), 17F (IL17F) in the formation of chronic hepatitis C infection. Patients and methods We classify the patients into two groups: the first group included 51 chronic HCV patients who did not take antiviral therapy (the study group) and the second group included 51 healthy blood donors (as a control group). The levels of IL17A and IL17F in the serum of both groups were measured using the sandwich enzyme-linked immunosorbent assay method. Results The serum values of IL17A were higher in patients with chronic HCV than the other group with the mean values being 52.9±32.6 pg/ml in the patient group and 17.1±10.4 pg/ml in the control group. IL17F was slightly higher in the HCV patient group than the control group, but it was statistically insignificant. Moreover, there were significant positive correlations between IL17A and alanine aminotransferase, viral load, and degree of liver fibrosis. Conclusion Patients with chronic HCV infections had a higher serum level of IL17A than the normal persons and it is positively correlated with alanine aminotransferase, viral load, and degree of liver fibrosis. This suggests its pivotal role in the formation of chronic HCV infection; so, it can be used as a new marker for disease progression due to its positive correlation with the severity of liver injury.